Memory Deficit in Patients With Temporal Lobe Epilepsy: Evidence From Eye Tracking Technology - Zhu, Guangpu; Wang, Jing; Xiao, Ling; Yang, Ke; Huang, Kailing; Li, Beibin; Huang, Sha; Hu, Bingliang; Xiao, Bo; Liu, Ding; Feng, Li; Wang, Quan (Frontiers in Neuroscience, 2021)
Objective: To explore quantitative measurements of the visual attention and neuroelectrophysiological relevance of memory deficits in temporal lobe epilepsy (TLE) by eye tracking and electroencephalography (EEG). Methods: Thirty-four TLE patients and twenty-eight healthy controls were invited to complete neurobehavioral assessments, cognitive oculomotor tasks, and 24-h video EEG (VEEG) recordings using an automated computer-based memory assessment platform with an eye tracker. Visit counts, visit time, and time of first fixation on areas of interest (AOIs) were recorded and analyzed in combination with interictal epileptic discharge (IED) characteristics from the bilateral temporal lobes. Results: The TLE patients had significantly worse Wechsler Digit Span scores (F (1,58) = 7.49, p = 0.008). In the Short-Term Memory Game with eye tracking, TLE patients took a longer time to find the memorized items (F (1,57) = 17.30, p < 0.001). They had longer first fixation (F (1,57) = 4.06, p = 0.049) and more visit counts (F (1,57) =7.58, p = 0.008) on the target during the recall. Furthermore, the performance of the patients in the Digit Span task was negatively correlated with the total number of IEDs (r (28) = -0.463, p = 0.013) and the number of spikes per sleep cycle (r (28) = -0.420, p = 0.026). Conclusions: Eye tracking appears to be a quantitative, objective measure of memory evaluation, demonstrating memory retrieval deficits but preserved visual attention in TLE patients. Nocturnal temporal lobe IEDs are closely associated with memory performance, which might be the electrophysiological mechanism for memory impairment in TLE.